2022
DOI: 10.3389/fphar.2022.1002871
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the role of dipeptidyl peptidase 8 and dipeptidyl peptidase 9 and their inhibitors

Abstract: Dipeptidyl peptidase 8 (DPP8) and 9 (DPP9) are widely expressed in mammals including humans, mainly locate in the cytoplasm. The DPP8 and DPP9 (DPP8/9) belong to serine proteolytic enzymes, they can recognize and cleave N-terminal dipeptides of specific substrates if proline is at the penultimate position. Because the localization of DPP8/9 is different from that of DPP4 and the substrates for DPP8/9 are not yet completely clear, their physiological and pathological roles are still being further explored. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 131 publications
0
10
0
Order By: Relevance
“…Therefore, considering the present study, the effect of apoptosis may be most important after DPP reduction. Nevertheless, certain studies have reported that DPP8/9 inhibitors can induce pyroptosis in cell experiments (23)(24)(25). Ferroptosis can be inhibited by blocking DPP4 activity (26).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, considering the present study, the effect of apoptosis may be most important after DPP reduction. Nevertheless, certain studies have reported that DPP8/9 inhibitors can induce pyroptosis in cell experiments (23)(24)(25). Ferroptosis can be inhibited by blocking DPP4 activity (26).…”
Section: Discussionmentioning
confidence: 99%
“…A potential explanation for this duality is that 1G244 inhibits DPP8 and DPP9 by different mechanisms. Indeed, it has been suggested that 1G244’s inhibition of DPP8 is based on binding that is slow and tight [ 21 ], i.e., irreversible [ 11 ], while its inhibition of DPP9 is competitive [ 21 ]. However, studies using experimental 3D models have not demonstrated clear differences between the molecular structures of 1G244-liganded DPP8 and 1G244-liganded DPP9 to support the suggested hypothesis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…DPP8 substrates include inflammatory protein-10 (IP10), interfering T-cell chemokines (ITAC), and chemokines stromal cell-derived factor (SDF-1) [ 10 ], while DPP9 cleaves C-X-C motif chemokine 10 (CXCL10/IP10), S100-A10, SET, nucleobindin-1 (NUCB1), and interleukin-1 receptor antagonist protein (IL-1RA) as substrates [ 8 ]. In addition, numerous studies have shown that DPP8/9 is involved in immune system regulation and inflammation by the cleavage of these substrates [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two emerging potential targets for the development of anticancer, anti-inflammatory, or even anti-Covid19 drugs are the intracellular dipeptidyl peptidases 8 (DPP8) and 9 (DPP9). [7] Both proteases share highly similar active site architectures, thereby turning the development of DPP8 versus DPP9 selective inhibitors into a challenge. [8] We recently reported a 4-oxo-βlactam compound (1) as a promising DPP8 and DPP9 inhibitor (Figure 1).…”
Section: Introductionmentioning
confidence: 99%